COMPARATIVE ANALYSIS OF AVAILABLE METHODS OF CLEANING AND DISINFECTION OF REMOVABLE PLATE PROSTHESES FOR THE ELDERLY AND SENILE - Yuri V. Chizhov; Andrey A. Radkevich; Pavel V. Mitrofanov; Tamara V. Kazantseva; Marina N. Babich; Vladimir V. Sokolovich (Siberian Journal of Life Sciences and Agriculture, 2022)
Objective. To analyze three methods of cleaning and disinfection of removable plate prostheses (protected by patents) available for elderly and senile persons with psychoneurological diseases living in boarding schools.